Preparation and Characterization of Polyhedral Octaphenylsilsesquioxane Modified Castor oil based Polyurethane - Yue Wen; Pingping Jiang; Jie Huang; Agus Haryono; Jianneng Deng; Zhiliang Cao (Jurnal Kimia Terapan Indonesia, 2018)
Vegetable oil-based polyurethanes were synthesized using castor oil (CO) as feedstock, which were characterized by their environmental friendly and renewable properties. Aiming to compensate for shortcomings of these materials, a series of polyurethane/polyhedral octaphenylsilsesquioxane (OPS) hybrids with different OPS contents were prepared by physical mixing in the solutions. Thereafter?chemical structure?morphology and thermal properties of hybrids were characterized through Fourier transform infrared spectrometer (FTIR), scanning electron microscope (SEM), differential scanning calorimetry (DSC), thermal gravimetric analyzer (TGA), tensile test techniques and static contact angle. The results show that the hybrid polyurethanes display both enhanced glass transition temperatures (Tg), initial decomposition temperature (Td5) and tensile strength with low OPS contents. While with high contents?these values decline with the severe aggregation of nano-particles as shown in the SEM images. Meanwhile, the hybrid polyurethanes displayed enhanced surface hydrophobicity as the contact angle with water revealed